ANALISIS FUNDAMENTAL SAHAM PT. SOECHI LINES TBK (SOCI) DAN PT. ADHI KARYA PERSERO (ADHI) : TINJAUAN KINERJA KEUANGAN DAN REKOMENDASI INVESTASI - Feren Melina Junita; Harti Budi Yanti (JURNAL LENTERA BISNIS, 2025)
This paper presents a comprehensive financial analysis of two publicly listed companies in Indonesia: PT Soechi Lines Tbk (SOCI) and PT Adhi Karya (Persero) Tbk (ADHI), over the five-year period from 2019 to 2023. These companies operate in distinct sectors—maritime transportation and shipbuilding for SOCI, and construction and infrastructure development for ADHI. The objective of this study is to assess and compare their financial performance using key financial ratios including Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Earnings per Share (EPS). Data were obtained from the companies’ audited annual financial statements and analyzed using quantitative methods. The findings show that SOCI maintained relatively stable performance throughout the five years, demonstrating healthy profitability, conservative capital structure, and resilience during the COVID-19 pandemic. In contrast, ADHI exhibited a more volatile performance, heavily influenced by macroeconomic factors and project execution cycles, with signs of recovery in profitability observed in 2023. The comparative analysis indicates that SOCI is more suitable for risk-averse investors seeking long-term stability, whereas ADHI presents a higher-risk, higher-return profile, ideal for aggressive investors capitalizing on the company’s recovery momentum. This study contributes to the body of knowledge in fundamental stock analysis and offers valuable insights for investors and financial analysts in making data-driven investment decisions in the Indonesian capital market.